Counseling with Assertive Exercise to Stimulate Student's Self Confidence - Lushi Delfriani; Chery Julida Panjaitan; Rita Sari (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2023)
Cases of bullying are no stranger to the world of education, bullying is to frighten or disturb weak people. Bullying behavior has a very bad impact on the victim, one example of the most severe impact that usually occurs on the victim is depression, lack of confidence, even to the point where someone dies. Therefore, this study aims to find out how the results of assertive training stimulate the victim's self-confidence. The data collection method uses observation, interviews and documentation. The data analysis method used is a qualitative method. The results of this study are assertive exercises to stimulate the victim's self-confidence by showing bullying videos that are the same as what he experienced. Next, place the victim in certain positions and then the researcher gives questions that aim to stimulate his self-confidence. Assertive exercises to stimulate the victim's self-confidence get good results. Victims who were previously afraid and insecure about their abilities, now show confidence and confidence in their abilities to deal with problems.